THE DEPICTION OF BEAUTY MYTH IN COELHO’S THE SPY (Sastra Inggris UNPAM, 2022)
The study aims to analyze the depiction of the beauty myth experienced by the main character in Coelho's novel, The Spy (2006). This analysis focuses on how beauty myth is depicted in the main character and how beauty myth succeeses in destroying the main character’s life. The writer uses the theory book, The Beauty Myth by Naomi Wolf (2002). In writing this study, the writer uses a qualitative method. The results of this study indicate that the image of beauty myth actually occurs in the main character in several ways such as personal and social point of view by giving the main character joy, money, power, jewelries, and valuables. However, quiet opposite, beauty myth also destroys the life of the main character very tragically as she has to be willing to trade all kinds of pleasures such as jewelries, beautiful dresses, and other valuables for sex which she cannot enjoy it even she must be executed without concrete evidence against her in the end of the story.Keywords: , Beauty, Feminism, The Beauty Myth, Women